Blended Learning in Revolution Industrial for Generation Z - Ety Youhanita; Ninies Eryadini; Ratna Nurdiana (CV ODIS, 2022)
The digital era is one of the eras resulting from the impact of the application of the industrial revolution; therefore, the increasingly sophisticated digital era will also force educators to move faster to follow the flow of technological developments that are currently happening because education today is very important for every human life that is the goal is to promote better intellectual property and social integrity. One of the results of technology development in the digital era that can be used in the learning process in the pandemic era is the combination of offline and online learning, more commonly known as blended learning. The blended learning model is applied in the learning process to support the independent learning program at the independent campus. The independent learning program is a challenge faced by universities in curriculum development in the industrial era 4.0 to produce graduates with new literacy skills. Furthermore, the graduates that will be produced fall into the category of Generation Z, where generation Z is a digitally literate generation, so the learning process must also be digital-based. The results of the application of blended learning are increased student motivation and increased student learning outcomes or increased student achievement in education policy courses.